Дослідження кочення рушіїв мостових агрозасобів по слідах постійної технологічної колії - Адамчук, В. В.; Булгаков, В. М.; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Kuvachov, Volodymyr; Головач, І. В.; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Ihnatiev, Yevhen (My University, 2020)
UK: Вивчити кореляційний зв’язок між показниками фізико-механічних властивостей ґрунтового сліду постійної технологічної колії та їх вплив на тягово-зчіпні властивості мостового агрозасобу. Методи. Експериментальні дослідження проводилися за загальноприйнятими та розробленими методиками і передбачали використання сучасного контрольно-вимірювального обладнання. Результати. За безрозмірний критерій оцінки кочення колеса спеціалізованого ширококолійного агрозасобу, що враховує його дотичну силу і опір, у роботі прийнято коефіцієнт fk опору його коченню. На підставі експериментальних досліджень та оброблення отриманих даних на ПК створено аналітичні вирази регресійних залежностей коефіцієнта опору коченню коліс від вологості, твердості і щільності сліду постійної технологічної колії і побудовано їх графіки. Результати експериментальних досліджень показали, що фізико-механічні властивості ґрунту в слідах постійної технологічної колії і коефіцієнт опору коченню коліс агрозасобу мають досить високий кореляційний зв’язок. Висновки. В результаті проведених досліджень встановлено, що фізико-механічні властивості ґрунтового сліду постійної технологічної колії істотно впливають на витрати енергії з подолання сил опору коченню коліс агрозасобу. Зі збільшенням вологості ґрунтового сліду постійної технологічної колії з 10 до 45% коефіцієнт опору коченню збільшується з 0,06 до 0,1 (66%). А оскільки витрати потужності на подолання сил опору при русі пропорційні величині fk, то на стільки ж відсотків зростають і витрати енергії. Зі збільшенням твердості від 2,8 до 4,5 МПа і щільності з 1,3 до 1,6 г∙см – 3 ґрунтового сліду коефіцієнт опору коченню коліс агрозасобу зменшується з 0,1 до 0,06. Також зі збільшенням твердості ґрунтового сліду постійної технологічної колії з 2,5 до 4,0 МПа інтенсивно зростає і величина коефіцієнта об’ємного зминання ґрунту — з 4,0 до 45,0 МПа. За подальшого збільшення твердості ґрунтового сліду коефіцієнт об’ємного зминання ґрунту майже не зростає. Для зменшення коефіцієнта опору коченню коліс при русі по ґрунтовому сліду постійної технологічної колії необхідно формувати її як недеформовану опорну поверхню, тоді опір коченню має щонайменше значення. EN: To study the correlation between the indicators of physicomechanical properties of the soil trace of the constant technological track and their influence on the traction properties of the bridge agricultural tool. Methods. Experimental studies were conducted according to generally accepted and developed methods and involved the use of modern control and measuring equipment. Results. As the dimensionless criterion for assessing the rolling of the wheel of a specialized wide-track agricultural tool, taking into account its tangential force and resistance, the coefficient fk of its rolling resistance is taken in the work. Based on experimental researches and processing of the received data on the personal computer analytical expressions of regressive dependences of the coefficient of rolling resistance of wheels on humidity, hardness, and density of a trace of a constant technological track are created and their graphic charts are constructed. The results of experimental studies have shown that the physicomechanical properties of the soil in the traces of a constant technological track and the coefficient of rolling resistance of agricultural tools have a fairly high correlation. Conclusions. As a result of the carried out researches, it is established that the physicomechanical properties of a soil trace of a constant technological track essentially influence energy expenses on overcoming forces of resistance to the rolling of wheels of agricultural tools. With an increase in the soil of moisture of the permanent technological track from 10 to 45%, the coefficient of rolling resistance increases from 0.06 to 0.1 (66%). And since the charges of power to overcome the forces of resistance during motion are proportional to the value of fk, the same percentage increases in energy consumption. With increasing hardness from 2.8 to 4.5 MPa and density from 1.3 to 1.6 g·cm–3 of the soil trace, the rolling resistance coefficient of the wheels of the agricultural tool decreases from 0.1 to 0.06. Also, with the increase in the hardness of the soil trace of the constant technological track from 2.5 to 4.0 MPa, the value of the coefficient of volumetric crushing of the soil — from 4.0 to 45.0 MPa. With the further increase in the hardness of the soil trace, the coefficient of volumetric shrinkage of the soil almost does not increase. To reduce the coefficient of rolling resistance of the wheels when moving on the ground track of a constant technological track, it is necessary to form it as an undeformed bearing surface, then the rolling resistance has the least value.
Research of rolling of engines of bridge-type agricultural tools on the trace of a constant technological track
Keywords: тягово-зчіпні властивості; моніторинг властивостей; щільність; твердість; опір коченню; експериментальні дослідження; traction properties; monitoring of properties; density; hardness; rolling resistance; experimental researches